2015
DOI: 10.1037/trm0000045
|View full text |Cite
|
Sign up to set email alerts
|

Life-review and PTSD community counseling with two groups of Vietnam War veterans.

Abstract: Vietnam War veterans are aging into their late 60s and early 70s. In spite of an increase in older treatment-seeking veterans, none of the recommended PTSD psychotherapy techniques emerging within the past 3 decades includes integration of a life span perspective. In an effort to bridge the gap between PTSD and life span perspective interventions, this article describes an exploratory random-assignment, partial cross-over feasibility study that compared 2 different sequences of life review and PTSD group thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Civil war refugees will eventually get old and need an age-adequate trauma treatment. There is already the idea to combine LRT and exposure therapy to veterans [57]. But also aging survivors of traumatisation in childhood or adolescence will become a larger group requiring psychotherapy as society is aging.…”
Section: Discussionmentioning
confidence: 99%
“…Civil war refugees will eventually get old and need an age-adequate trauma treatment. There is already the idea to combine LRT and exposure therapy to veterans [57]. But also aging survivors of traumatisation in childhood or adolescence will become a larger group requiring psychotherapy as society is aging.…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing these stories through song and lyrics was described as giving another perspective to hear the same story potentially in a different way where others could truly listen and potentially have a better understanding. One study by Daniels et al (2015) found that a group of US Vietnam Veterans who participated in a facilitated reminiscence group showed greater improvement with PTSD symptoms in comparison to a standard psychotherapy group. Although this study was the only study known to this author that specifically looked at the impact of storytelling on military related PTSD, it does well in suggesting that the peer sharing of self-narratives focused on trauma in a group of peers has value for enhancing standard PTSD treatments.…”
Section: Listening To the Songsmentioning
confidence: 99%
“…When these fragments affect a veteran's perception of reality, they may find themselves stuck between worlds of past, present, and future. Studies have shown that songwriting (Baker et al, 2015;Tamplin et al, 2016), the telling and sharing of personal stories (Caddick et al, 2015;Daniels et al, 2015), and group music therapy (Bensimon et al,, 2012;Carr et al, 2012) have an influence on helping our minds restructure a positive sense of self in order to enhance or reestablish resiliency factors that could help find meaning again.…”
mentioning
confidence: 99%
“…Life review is a method of narrative therapy and is often applied to psychotherapy. The object of implementation has also moved on from older adults to expand its scope of application to include different age groups [ 23 , 24 , 25 , 26 ]. The clinical application of narrative therapy focuses on meaning-making, allowing the individual to interpret his/her own problems through dialogue.…”
Section: Introductionmentioning
confidence: 99%